Socio-Demographic and Cultural Factors Associated with The Occurrence of Low Birth Weight in Kupang - Simplicia Maria Anggrahini; Hari Basuki Notobroto; Rika Subarniati Triyoga (Health Notions, 2018)
The prevalence and death due to low birth weight (LBW) is still high in Kupang. There are multifactorial causes of LBW which can be categorized into: physical and social environment, mother, fetus, placenta and umbilical cord, and health service. From maternal factors, there are sub-factors of maternal characteristic such as knowledge of pregnancy, maternal health status, and the behavior of pregnancy care. The behavior of pregnancy care can be in the form of a traditional pregnancy care, which may lead to LBW. Most researches on the risk factor of LBW are related to clinical medical factors. This research aimed to determine the socio-demographic and cultural factors which are related to the occurrence of LBW in Kupang. This research used analytic observational method with case-control design, on 50 mothers giving birth to LBW and 50 mothers who delivered normal babies, through interview and tracing of maternal and infant medical records. To eliminate the clinical factors of medical causes of LBW (anemia, hypertension, pre-eclampsia, and infection), inclusion criterion was applied, as follows: mothers who give birth to normal childbirth, single infants, and have received integrated Antenatal Care (ANC) service. Exclusion criteria were: mothers give birth to twisted umbilical cord, placental weight <500 grams, infant with congenital defect, and incomplete medical records. This research took place at Prof. DR. W.Z. Johannes Hospital, Dedari Hospital and 2 Public Health Center in Kupang. Data analysis used logistic regression. The final results of logistic regression model of this study founded 5 variables that affect the occurrence of LBW in Kupang, beside the medical clinical factors, such as: maternal age, maternal education, BMI, increase the body weight during pregnancy, and heavy work during pregnancy. Keywords: Socio-demographic factors, Cultural factors, Low birth weight